Utility of a Paediatric Bleeding Questionnaire as a screening tool for von Willebrand disease in apparently healthy children. (16th May 2015) - Mittal, N.; Naridze, R.; James, P.; Shott, S.; Valentino, L. A.
<x xml:space="preserve">Abstract</x> Summary von Willebrand disease (VWD), an inherited bleeding disorder caused by deficiency or dysfunction of von Willebrand factor (VWF) is diagnosed when a personal and often a family history of excessive mucocutaneous bleeding is present along with abnormal laboratory studies. An accurate assessment of haemorrhagic symptoms is key in suspecting VWD but presents a challenge especially in children due to overlap between normal and abnormal bleeding. Bleeding questionnaire (BQ) scores have been validated in adults and have recently been validated in children with VWD for assessing bleeding severity. However, there are limited data supporting their use prospectively in healthy children with bleeding complaints. Aim The objectives of this study were to obtain normative data from children and validate a paediatric BQ (PBQ) to determine the discriminative ability of its total score and its individual components for identifying children likely to have VWD. Methods The PBQ was administered to 1281 multiethnic, healthy children between 30 days and 18 years of age presenting to a general paediatric office and to 35 children with VWD based on VWF antigen, activity and multimer pattern. Results When children with total BQ scores of 3 or more were predicted to have VWD, the sensitivity was 97.2%, the specificity was 97.1%, the positive predictive value was 48.6% and the negative predictive value was 99.9%. Conclusions The PBQ may help discriminate a significant bleeding history from trivial bleeding, may be integrated into the primary care algorithm for evaluating children suspected with VWD.